ICTs in Language and Literacy Education in Bangladesh: A Critical Review - Sardar M. Anwaruddin (Arizona State University, 2015)
The advancement of information and communication technologies (ICTs) has challenged the traditional notion of literacy as print-based reading and writing. In this article, I discuss why integration of ICTs into language and literacy curricula is important from the perspectives of the pedagogy of multiliteracies and sociocultural theories of learning. After reviewing the state of ICT use in language and literacy education in Bangladesh, I argue that the use of ICTs does not automatically guarantee improved student learning. On the contrary, it may reify transmission models of education and situate teachers and students in certain identity positions as passive consumers of pre-packaged curricula. Building on Althussers notion of interpellation, I give an example of how a top-down ICT-integrated curriculum may severely restrict teachers and students agency to interrogate assumptions about power and politics around schooling and to develop a language of critique and hope. I conclude the article with a call for integrating the principles of critical pedagogy into teachers professional development programs so that teachers may learn to use ICTs in liberatory ways.